Digital Technology-Assisted Deep Learning in Language Classes: Exploring EFL Teachers’ Perspectives of Students with Disabilities - Tusino (Proceeding International Conference on Education, 2025)
Although numerous studies have investigated digital technology-assisted deep learning in English as a foreign language (EFL) classes, only a few were conducted for students with disabilities. This study aims to explain teachers’ perceptions regarding technology-assisted deep learning in English learning. This study employed a qualitative case study with six EFL teachers of the special schools in Indonesia. Data were collected through semi-structured interviews. Teachers’ responses towards attitudes, perceived benefits, and challenges of digital technology-enhanced deep learning practices were analyzed through a thematic analysis. Findings revealed that EFL teachers had positive attitudes towards digital technology-assisted deep learning in language classes. It was also found that digital technology-assisted deep learning supported students’ learning autonomy and engagement. However, the results of the study identified several challenges such as lack of suitable digital materials and technical constraints in classroom settings.  The findings highlight that digital technology-assisted deep learning is a potential learning model to enhance students’ autonomous learning for special education.